2016
DOI: 10.1177/1533034615626614
|View full text |Cite
|
Sign up to set email alerts
|

Customized Tool for the Validation of Optical Coherence Tomography in Differentiation of Prostate Cancer

Abstract: We successfully designed and applied a customized tool to process radical prostatectomy specimens to improve the coregistration of whole mount histology sections to fresh tissue optical coherence tomography pullback measurements. This technique will be crucial in validating the results of optical coherence tomography imaging studies with histology and can easily be applied in other solid tissues as well, for example, lung, kidney, breast, and liver. This will help improve the efficacy of optical coherence tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
0
16
1
Order By: Relevance
“…Different from our previous ex-vivo studies, [12,23,24] the light seems to penetrate deeper in vivo for stroma compared with the Gleason patterns. This difference in penetration depth should be exploited in future studies by determining the optical attenuation coefficient.…”
Section: Comparing In Vivo Oct With Previously Published Atlascontrasting
confidence: 94%
See 1 more Smart Citation
“…Different from our previous ex-vivo studies, [12,23,24] the light seems to penetrate deeper in vivo for stroma compared with the Gleason patterns. This difference in penetration depth should be exploited in future studies by determining the optical attenuation coefficient.…”
Section: Comparing In Vivo Oct With Previously Published Atlascontrasting
confidence: 94%
“…This difference in penetration depth should be exploited in future studies by determining the optical attenuation coefficient. [12,23,24] The possibility of collecting good quality images of the prostate with needle-based OCT measurements is now the first successful step towards a larger cohort study that aims to correlate OCT with histology to set up in vivo discriminative parameters. [13] By using two highly selected patients with PCa prior to this proposed correlation study, we follow the IDEAL recommendations [25].…”
Section: Comparing In Vivo Oct With Previously Published Atlasmentioning
confidence: 99%
“…Four (in a small prostate) or six (in a large prostate) intravascular (IV)-catheters were placed in the prostate using the customized tool as described in previous work. 25 After removal of the insertion needle, the C7 dragonfly tm OCT probe was inserted into the in-situ transparent IV catheter and OCT measurements of the prostate tissue were acquired.…”
Section: Test Methodsmentioning
confidence: 99%
“…The second part of the protocol enables one to one comparison of in vivo data with histology for both CLE and OCT. Our approach is similar to the approach of Muller et al [28], which compared ex-vivo needle-based OCT measurements of radical prostatectomy specimens with histology very precisely by cutting through the measurement trajectories. In our measurements data will be obtained from invivo tissue, in which red blood cells will absorb and scatter light different from regular cells.…”
Section: Benefits and Risksmentioning
confidence: 99%
“…A limited number of studies has looked at OCT's diagnostic role in differentiating benign and malignant microscopic tissue of the prostate gland. Muller et al demonstrated with the use of a histopathological validation tool that ex-vivo needle-based OCT measurements of radical prostatectomy specimens can differentiate between cancer and healthy prostate tissue [27][28][29]. The quantitative analysis of OCT signal by means of the attenuation coefficient was significantly higher in malignant compared to benign tissue with an area under the curve ranging from 0.64 -0.89 depending on the histopathological analysis used [29].…”
mentioning
confidence: 99%